Theoretical Study of Gas Adsorption on Metal Doped Single Wall Carbon Nanotube - ทับทิมใส, ฌาณุกรณ์ (KKU Science Journal, 2013)
Carbon nanotubes are novel nanomaterials which have the excellent mechanical, thermal and electronic properties. High surface area of carbon nanotubes can be developed to be material for clean energy storage or toxic gas sensor. The theoretical study of gas adsorption on carbon nanotube is reviewed. The results reveal that gas can absorb on defected carbon nanotube stronger than that of pristine carbon nanotube. Metal doping on carbon nanotubes can improve the gas adsorption abilities of the tubes. Moreover, the structural and electronic properties of gas adsorption on pristine and metal doped carbon nanotubes are also reported.